Triple bottom line and sustainable performance measurement in industrial companies - Flavio Hourneaux Jr; Marcelo Luiz da Silva Gabriel; Dolores Amalia Gallardo-Vázquez (REGE Revista de Gestão, 2018)
Purpose - The purpose of this paper is to propose a minimum set of indicators to be measured by industrial companies to represent the triple bottom line (TBL) approach. Design/methodology/approach - The research is both descriptive and quantitative. Three hypotheses establish associations among the degrees of use of TBL indicators and their different degrees of use in firms. The authors used confirmatory factor analysis (CFA) to validate the scale and structural equation modelling to represent the final measurement model. The survey gathered 149 industrial companies. Findings - The results pointed out that there are positive associations among the degree of use of environmental indicators and social indicators, economic, environmental and social indicators have different degrees of use in firms, a positive association between the degree of use of environmental and social indicators and the use of economic indicators was not confirmed. The findings suggest how to measure sustainable performance for industrial companies and highlight the differences in the degree of use for the three dimensions of TBL. Research limitations/implications - The limitations refer to the non-probabilistic sample, applied in a specific context, industrial companies. Practical implications - This set of indicators is intended to be used by industrial companies as a reliable instrument to sustainable performance assessment of the current stage of the TBL deployment and provide alternative approaches to address specific issues related to the environmental, social and economic sustainability. Social implications - The results offer tangible results for measuring and reporting firm’s social and environmental performance. Originality/value - This paper intends to offer an integrated and consistent way of measuring sustainability in industrial companies.